Rhinovirus and asthma: Challenges and opportunities. (20th November 2020) - Ortega, Hector; Nickle, David; Carter, Laura
Summary: Human rhinoviruses (RVs) are the primary aetiological agent of the common cold. Generally, the associated infection is mild and self‐limiting, but may also be associated with bronchiolitis in infants, pneumonia in the immunocompromised and exacerbation in patients with pulmonary conditions such as asthma or chronic obstructive pulmonary disease. Viral infection accounts for as many as two thirds of asthma exacerbations in children and more than half in adults. Allergy and asthma are major risk factors for more frequent and severe RV‐related illnesses. The prevalence of RV‐induced wheezing will likely continue to increase given that asthma affects a significant proportion of the population, with allergic asthma accounting for the majority. Several new respiratory viruses and their subgroups have been discovered, with various degrees of relevance. This review will focus on RV infection in the context of the epidemiologic evidence, genetic variability, pathobiology, clinical studies in the context of asthma, differences with other viruses including COVID‐19 and current treatment interventions.